ANALISIS PRAANGGAPAN DALAM NOVEL â€œIN A BLUE MOONâ€ KARYA ILANA TAN - Dondokambey, Ester Graceshella; Karamoy, Olga H.S.; Pandean, Mariam L.M. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2020)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â  Â This research is entitled "Analisis Praanggapan dalam novel In a Blue Moon karya Ilana Tan". This research discusses what kinds of presuppositions exist in the novel In a Blue Moon. The purpose of this research is to identify, classify, and analyze the types of presuppositions in the novel In a Blue Moon. The research data were taken from inter-character utterances containing presuppositions in the novel. The data is then analyzed using George Yule's theory. The method used in this research is qualitative method. The results of this study found all kinds of presuppositions in the novel In a Blue Moon, based on Yule's theory. Starting from existential presuppositions, marked by the use of nominal and pronominal (-ku) phrases in speech. Then factive presuppositions, characterized by the use of verbs, adjectives, adverbs, and nouns. Furthermore, lexical presuppositions are characterized by the use of prepositional phrases, nominal phrases, verbs, as well as adverbs. Furthermore, structural presupposition is characterized by the use of the word question what, when, who, how, and why. Meanwhile, for non-factual presuppositions, it is marked by the use of verbs, and for counterfactual presuppositions, it is marked by conjunction.Keywords: Pragmatics, Presuppositions, Novel â€œIn a Blue Moonâ€.